2013
DOI: 10.1016/j.cmet.2013.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Desnutrin/ATGL Activates PPARδ to Promote Mitochondrial Function for Insulin Secretion in Islet β Cells

Abstract: Excessive caloric intake leading to obesity is associated with insulin resistance and dysfuntion of islet β cells. High fat feeding decreases desnutrin (also called ATGL/PNPLA2) levels in islets. Here we show that desnutrin ablation via RIP-Cre (βKO) or RIP-CreER results in hyperglycemia with impaired glucose-stimulated insulin secretion (GSIS). Due to decreased lipolysis, islets have higher TAG content but lower free FA levels. βKO islets exhibit impaired mitochondrial respiration and lower production of ATP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
99
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(116 citation statements)
references
References 46 publications
13
99
4
Order By: Relevance
“…In striking contrast to this highly dynamic regulation of lipolysis, recent stable isotope studies in human skeletal muscle have suggested that basal lipolytic rates in muscle are relatively high and that free fatty acids entering the myocytes necessarily traffic via the intramyocellular TAG stored within LDs before being oxidized (7). Concordant observations were also recently reported in cardiomyocytes, hepatocytes, and islets (8)(9)(10). How, then, are these important functional differences mediated?…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…In striking contrast to this highly dynamic regulation of lipolysis, recent stable isotope studies in human skeletal muscle have suggested that basal lipolytic rates in muscle are relatively high and that free fatty acids entering the myocytes necessarily traffic via the intramyocellular TAG stored within LDs before being oxidized (7). Concordant observations were also recently reported in cardiomyocytes, hepatocytes, and islets (8)(9)(10). How, then, are these important functional differences mediated?…”
Section: Discussionsupporting
confidence: 54%
“…The situation in the liver is more complex, because here neutral lipids can be repackaged into lipoproteins for subsequent export (6). Intriguing work by several groups has recently suggested that fatty acids traffic via the LDs in myocytes (7), cardiomyocytes (8), hepatocytes (9), and pancreatic islets (10). These studies also imply and, in some cases (7) actually demonstrate, that this is a somewhat more constitutive process than in adipocytes, raising the question of exactly how lipolysis is coordinated in these cells, which under normal circumstances do not express perilipin 1.…”
mentioning
confidence: 99%
“…PEPCK and GYK are both PPAR and cAMP response element targets, which may explain their differential regulation among the adipose tissue depots (see below). Recent work from various labs indicates that lipolysis also contributes to cellular signaling events ( 10,11,14,41 ) by providing ligands for PPAR ␣ and ␦ , which in turn serve to match lipid oxidation with supply ( 9 ). We therefore reasoned that lipolysis was also driving the increase in lipogenesis and oxidation, and we tested this by deleting ATGL in adipose tissue of adult mice using an inducible model.…”
Section: Discussionmentioning
confidence: 99%
“…ATGL-mediated lipolysis is also required for functional PPAR-α and PPAR-δ signaling in oxidative tissues and the pancreatic β-cell, respectively (16,(33)(34)(35). For example, absence of ATGL in cardiac muscle leads to reduced PPARα-mediated mitochondrial biogenesis, substrate oxidation, and respiration, resulting in the lethal cardiomyopathy (16).…”
Section: Discussionmentioning
confidence: 99%